Konsep Pendidikan Karakter Dalam Pandangan Jalaluddin Rumi (Studi Kitab Fihi Ma Fihi) - Ardian Fatkhurohman; Gunawan Ikhtiono; Noneng Siti Rosidah (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
Character education in Islamic religious teachings is a rule for doing good deeds stated in the Qur'an and Al-Hadith. The essence of Islamic teachings is noble morals that rests on a harmonious and balanced relationship between humans and God, and between humans and humans. Character education in Islamic religious teachings is a rule for doing good deeds stated in the Qur'an and Al-Hadith. Abuddin Nata said that the core of Islamic teachings is noble morals that rest on a harmonious and balanced relationship between humans and God, and between humans and humans. This research is a qualitative research, the data presented is in the form of descriptive data obtained through books that are relevant to the object of study. The results of this research found character education in Maulana Jalaluddin Rumi's view through his work entitled Fihi Ma Fihi, including religious, noble character, loving knowledge, skilled (capable), creative, democratic, responsible, and hardworking.